Challenges and opportunities in real‐world evidence on the renal effects of sodium‐glucose cotransporter‐2 inhibitors - Fadini, Gian Paolo; Del Prato, Stefano; Avogaro, Angelo; Solini, Anna (Diabetes, obesity & metabolism, 2022)
With increasing population aging and prevalence of type 2 diabetes (T2D) worldwide, prevention of diabetic complications remains a major unmet need. While cardiovascular outcomes of diabetes are improving over time, diabetic kidney disease (DKD) still leads to an exceedingly high rate of end‐stage kidney disease (ESKD). A game‐changing opportunity is offered by treatment with sodium‐glucose cotransporter‐2 (SGLT2) inhibitors. Randomized controlled trials (RCTs) have indisputably shown that SGLT2 inhibitors reduce the rate of DKD progression, the decline in estimated glomerular filtration rate (eGFR), and the development of ESKD. In parallel, SGLT2 inhibitors improve cardiovascular outcomes, especially the risk of hospitalization for heart failure. Real‐world studies (RWSs) have largely confirmed the findings of RCTs in broader populations of subjects with T2D followed under routine care. In the present paper, we review RWSs exploring the renal effects of SGLT2 inhibitors and highlight the most critical challenges that can be encountered in designing and conducting such studies. Channelling bias (confounding by indication), time‐lag bias, conditioning on the future, database heterogeneity, linearity of eGFR change over time, and duration of observation are critical issues that may undermine the robustness of RWS findings. We then elaborate on the new opportunities to overcome such limitations by describing the design and objectives of the DARWIN (DApagliflozin Real‐World evIdeNce)‐Renal study, a new RWS promoted by the Italian Diabetes Society. Fine‐tuning of methods for comparative observational research will improve evidence derived from RWSs on the renal effects of SGLT2 inhibitors, aiding the evolving discussion regarding the place of SGLT2 inhibitors in T2D treatment algorithms in different stages of DKD.